Rural Women Farmers and Sustainable Livelihoods in Guyana - Henry, Paulette (International Journal of Scientific Research and Management (IJSRM), 2021)
Rural women in agriculture are legitimized women as productive stakeholders through a process that documents the various roles have played in rural agriculture, the rural economy, and food security. Accounting for 43% of the world’s agricultural labor force, women are important actors in the achievement of Sustainable Development Goal 2 particularly in reducing poverty especially among women, and improving food security. This quantitative study has shown that women have combined their roles in varying fields of agriculture using their income to take care of families while contributing to the economy and food security. Their contributions however are underrecognized due to the gender disparities in the investments made to their male peers in the same business. This may be due to the feminization of rural agriculture coupled with many women not having the literacies required to negotiate the demands of land or loan acquisition and the technical skills to move beyond subsistence agriculture. Notwithstanding, rural women farmers earn income that helps to guarantee the basic livelihoods of their families and contribute to community food security. However, rural women farmers also have limited financial and technical capabilities to conserve their surpluses and increase their economic well-being.  Investments by national governments must be made to rural agriculture with specific recognition towards the advancement of women farmers.